2016
DOI: 10.1111/mpp.12393
|View full text |Cite
|
Sign up to set email alerts
|

Plant hormones: a fungal point of view

Abstract: SUMMARYMost classical plant hormones are also produced by pathogenic and symbiotic fungi. The way in which these molecules favour the invasion of plant tissues and the development of fungi inside plant tissues is still largely unknown. In this review, we examine the different roles of such hormone production by pathogenic fungi. Converging evidence suggests that these fungal-derived molecules have potentially two modes of action: (i) they may perturb plant processes, either positively or negatively, to favour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
216
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(228 citation statements)
references
References 141 publications
5
216
0
7
Order By: Relevance
“…Adequate consideration of root architecture, root anatomy, and the spatiotemporal distribution of roots and fungal propagules would be useful. Also, defining the relative importance of root phenotypes in the context of other plant phenotypes affecting root–microbe interactions such as plant phytohormone signalling (Chanclud & Morel, ; Pozo, López‐Ráez, Azcón‐Aguilar, & García‐Garrido, ; Venturi & Keel, ) deserves attention.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate consideration of root architecture, root anatomy, and the spatiotemporal distribution of roots and fungal propagules would be useful. Also, defining the relative importance of root phenotypes in the context of other plant phenotypes affecting root–microbe interactions such as plant phytohormone signalling (Chanclud & Morel, ; Pozo, López‐Ráez, Azcón‐Aguilar, & García‐Garrido, ; Venturi & Keel, ) deserves attention.…”
Section: Discussionmentioning
confidence: 99%
“…Different fungi, both pathogenic or symbiotic, have been reported to produce CKs (Crafts and Miller, 1974; Murphy et al, 1997; Jameson, 2000; Chanclud and Morel, 2016). We have shown that L. maculans produces a wide spectrum of CKs in vitro , present both in the mycelium ( Figure 1 ) and culture medium (Supplementary Figure 1), as well as in planta upon infection in B. napus ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, effectors can modulate the host’s metabolism and directly influence defense reactions thus helping with establishing compatible interactions [57]. In addition to these proteinaceous effectors, secreted fungal low-molecular weight compounds like reactive oxygen species [8] or secondary metabolites, like plant hormones [9] have turned out to be important for compatible interactions.…”
Section: Introductionmentioning
confidence: 99%